Use of filtration and electricity analogy in simulation of underflooding protection in urban construction - V. I. Sologaev (Вестник СибАДИ)
Introduction. The fight against underflooding remains an urgent problem. The application of the analogy between water filtration and electric current has the goal of protecting the environment, built-up areas and, in particular, highways in cities from underflooding. Writing Ohm’s law similarly to Darcy’s filtration law, we achieve a better match to their analogy. This, in turn, makes it possible to develop new technologies for protection against underflooding in urban construction, for example, electroosmotic dewatering and its modeling. Such technologies make it possible to drain clayey soils.Methods and materials. Darcy’s law, Ohm’s law and the law of electroosmotic filtration are considered together. A methodology for modelling construction dewatering is given, taking into account the combined effect of the two physical laws of water filtration and electroosmosis, optimally combining the high-altitude geometric arrangement of drainage bases and contact electrodes. The options for draining clay soil under the action of an electric field are presented. With the combined use of gravitational forces and electric direct current forces in the drained soil, the total filtration rate is the sum of the Darcy’s law component and another component of the water velocity – electroosmotic filtration. An additional feature of joint modelling in a porous medium of water filtration and electroosmosis is that the mass of the water-resistant part of the soil and its part related to the dielectric may not coincide. This complexity of the model is overcome by dividing it into modules, which can then be combined in compliance with the balance principle, stitching modules along the boundaries. To continue the scientific discussion, a short but informative overview of international publications on the topic under consideration is given.Discussion. The methodology for complex calculation and modelling of the joint processes of water filtration in soils, the flow of electric current and electroosmotic filtration can find useful application in the development of effective protection against underflooding in urban construction. a sequence of algorithmic modelling steps is recommended. initially, it is recommended to run rough spreadsheet simulations on personal computers and mobile phones. next, a different modelling approach should be applied. based on the initial rough models of the previous step, it is necessary to write the algorithms in the programming language. the compiled model of the investigated filtration and electroosmosis processes will significantly increase the reliability of the design of protection against underflooding.conclusion. a comparison is made of the joint use of construction dewatering means of different physical essence, with simultaneous processes of gravitational filtration of underground water and passing a direct electric current through the drained soil, which causes an additional effect of electroosmosis. it is proposed to apply in a new way the analogy of water filtration and electric current in order to achieve more effective results of engineering activities by modeling protection against underflooding of building areas, ensuring the safety of urban construction when the level of groundwater rises.